Designing a Knowledge-Based Smart Community System to Strengthen Community Governance - Fahmy Habib Hasanudin; Fandi Achmad; Hilman Dwi Anggana; Dio Pasa Pramudis; Muhammad Rivaldi; Muhamad Daffa Rial (Telkom University, 2026)
The development of digital technology drives the need for more transparent, participatory, and data-driven community administration. However, in many residential communities, administrative management is still carried out manually, fragmented, and lacks knowledge documentation, potentially leading to inefficiency and low community participation. This study aims to design and implement a Smart Community Platform based on data and knowledge management as an appropriate technology to improve administrative transparency and community participation in the Paguyuban Arcadia, G-Land Arcadia area, Bandung Regency. The research method used is a participatory approach and Rapid Application Development (RAD), which includes the stages of needs planning, system design, prototype development, and system implementation and evaluation by involving administrators and residents as users. The results of the study indicate that the implementation of the Smart Community Platform can improve the transparency of administrative information, the efficiency of citizen data management, and the intensity of community participation through e-administration features, digital forums, and data-based information notifications. In addition, the implementation of knowledge management contributes to documenting and distributing community knowledge in a structured manner. The implications of this research show that the integration of digital technology, data, and knowledge management in the context of local communities can be a model for strengthening sustainable and adaptive community governance to digital transformation.